Power Interplay Between Executive and Legislative in the Formation of Undang-Undang Nomor. 3 Tahun 2022 Concerning Ibu Kota Negara - Mahardika Agustin, Mutiara; Ilmar, Anwar (Dinasti Research, 2024)
The main objective of this research is to discuss the power interplay between the executive and legislature in the formation of Law no. 3 of 2022 concerning Ibu Kota Negara. With a focus on the interaction of power between the two institutions in the process of forming the IKN Law. This research uses qualitative methods and is explained using the power cube theory by John Gaventa. In the formation of this law, most of the factions in the DPR RI out of a total of 9, only one opposition party refused to accept and approve the discussion of the IKN Bill. With the position of the government which has a large coalition (grand coalition) with membership in parliament reaching 74%. It can be seen that the role of the executive is more dominant than the role of the legislature in determining the direction of decisions on this Law, namely by conditioning the decisions taken by party factions that are members of supporting government supporters to fully support them.